Natural Compounds as Guides for the Discovery of Drugs Targeting G-Protein-Coupled Receptors - Joan Serrano-Marín; Irene Reyes-Resina; Eva Martínez-Pinilla; Gemma Navarro; Rafael Franco (Molecules, 2020)
G protein-coupled receptors (GPCRs), which constitute the most populous family of the human proteome, are the target of 35–45% of approved therapeutic drugs. This review focuses on natural products (excluding peptides) that target GPCRs. Natural compounds identified so far as agonists, antagonists or allosteric modulators of GPCRs have been found in all groups of existing living beings according to Whittaker’s Five Kingdom Classification, i.e., bacteria (monera), fungi, protoctists, plants and animals. Terpenoids, alkaloids and flavonoids are the most common chemical structures that target GPCRs whose endogenous ligands range from lipids to epinephrine, from molecules that activate taste receptors to molecules that activate smell receptors. Virtually all of the compounds whose formula is displayed in this review are pharmacophores with potential for drug discovery; furthermore, they are expected to help expand the number of GPCRs that can be considered as therapeutic targets.